Industrial and Pharmaceutical Applications of Microbial Diversity of Hypersaline Ecology from Lonar Soda Crater - Bawane, Pradip; Deshpande, Shirish; Yele, Santosh (Current Pharmaceutical Biotechnology, 2024)
The unidentified geochemical and physiochemical characteristics of Soda Lakes across the globe make it a novel reservoir and bring attention to scientific civic for its conceivable industrial and pharmaceutical applications. In India, in the Maharashtra state, Lonar Lake is a naturally created Soda Lake by a meteorite impact. Phylogenetic data from this lake explored a diverse array of microorganisms like haloalkaliphilic bacteria and Archaea. Previously reported studies postulated the major microbial communities present in this lake ecosystem are Proteobacteria, Actinobacteria, Firmicutes, and Cyanobacteria. Furthermore, it also contains Bacteroidetes, Nitrospirae, and Verrucomicrobia. This lake is also rich in phytoplankton, with the predominant presence of the Spirulina plantensis. Unique microbial strains from Lonar Lake ecosystems have fascinated consideration as a source of biological molecules with medicinal, industrial, and biotechnological potential. Recent literature revealed the isolation of antibioticproducing bacteria and alkaline proteases-producing alkaliphilic bacterium, as well as novel species of rare methylotrophs, other bacterial strains involved in producing vital enzymes, and unique actinomycetes are also reported. It indicates that the novel bacterial assemblage not reached hitherto may exist in this modified and unique ecology. This comprehensive review provides information about microbial diversity and its industrial and pharmaceutical interests that exist in Lonar Lake, which could be the future source of bioactive enzymes, biosurfactants, and biofuel and also useful in bioremediation. Furthermore, the novel species of microorganisms isolated from Lonar Lake have applications in the biosynthesis of medicines like antibiotics, antivirals, antifungals, anti-inflammatory agents, and precursors for synthesising valuable products. Data consolidated in the present review will cater to the needs of emerging industrial sectors for their commercial and therapeutic applications.
Keywords: proteobacteria